Modelling And Control Of A Fixed Calliper-Based Electronic Wedge Brake - Ahmad, Fauzi; Hudha, Khisbullah; Mazlan, Saiful Amri; Jamaluddin, Hishamuddin; Zamzuri, Hairi; Abd Kadir, Zulkiffli; Aparow, Vimal Rau (Assoc. Of Mechanical Eng. And Technicians Of Slovenia, 2017)

(untitled)
This paper presents a new design of an electronic fixed calliper-based wedge brake system.The movement of both sides of the brake piston is activated by a wedge block mechanism.The proposed fixed calliper-based electronic wedge brake system is a class of hydraulic-free device. The mechanism consists of two sets of wedge blocks,a ball screw drive shaft,a sliding beam and an electric motor.In this mechanism,the rotation of the shaft of the electric motor is converted into linear motion by using a ball screw drive shaft while the linear motion of the drive shaft will force the sliding beam to be displaced linearly.This will activate the wedge mechanism,which will cause the pad to be displaced tangentially to the disc brake.The movement of the pad in pressing the disc will generate clamping force and produce brake torque when the wheel rotates.In this study,the mathematical model of the system that generates the clamping force was identified.The model was based on a second order transfer function.The proposed mathematical model was then validated experimentally using a brake test rig installed with several sensors and input-output (IO) device.The performance of the brake mechanism in term of rotational input of the drive shaft and clamping force produced by the brake were observed.Accordingly,a torque tracking proportional-integral-derivative (PID) control of the system was proposed and studied through simulation and experiment.Comparisons between experimental results and model responses were made.It is found that the trend between simulation results and experimental data are similar,with an acceptable level of error.